Directing gender equality in Ahmed Yerima’s Altine’s Wrath - Edum, Sunday (Journal of Gender and Power, 2021)
One of the functions of the theatre director is to develop a concept that would appeal to the audience in the process of his interpretation. This paper textually evaluates the issue of gender equality as the directorial concept in Ahmed Yerima’s Altine’s Wrath. The paper adopts the sociological, literary and artistic methods to interrogate the directorial implications of the text as it will be demonstrated in the performance. The paper notes that a thorough understanding of gender theories and principles would guide a director’s realization of the identified concept. The paper, therefore, calls on directors to support the issue of gender equality by developing concepts in this regard and as such promote a peaceful society.